Crystal-plastic deformation of zircon: A defect in the assumption of chemical robustness - Reddy, Steven; Timms, Nicholas Eric; Kinny, Peter; Buchan, Craig; Trimby, P.; Blake, K. (Geological Society of America, 2006)
Orientation contrast imaging and quantitative electron backscatter diffraction analysis of a zircon collected from an Indian Ocean gabbro reveal intragrain crystallographic misorientations (up to 14°) and low-angle orientation boundaries concentrated in the zircon tips. These features represent the formation and migration of dislocations and provide the first evidence of crystal-plastic deformation of zircon under crustal conditions. Panchromatic and wavelength cathodoluminescence (CL), combined with quantitative rare earth element (REE) ion microprobe analyses, demonstrate modification of zircon REE chemistry within the areas of crystal plasticity. These data indicate that the enhanced diffusion of REEs into the zircon is spatially linked to the presence of dislocations which behave as high-diffusivity pathways, increasing bulk diffusion rates and effective diffusion distances in the zircon by several orders of magnitude. In addition, discrete c.2?m zones of reduced panchromatic CL correspond exactly to the position of low-angle orientation boundaries and demonstrate a defect dependence on CL signal at high dislocation densities. The presence of deformation-related crystal-plastic microstructures in zircon, and their role in modifying elemental diffusion, questions the commonly made assumption of chemical robustness and has fundamental implications for the interpretation of zircon trace-element and isotopic data.